Motor Third Party Liability after CJEU Interpretation of the Directive 103/2009/EC in Vnuk Judgment - Shevchenko, Olga (Teisė, 2019)
[full article, abstract in English; abstract in Lithuanian]The aim of this article is to assess the consequences of the interpretation of the terms ‘vehicle’ and ‘use of a vehicle’ in the light of the case of Damijan Vnuk v Zavarovalnica Trigalev (C-162/13) the Court of Justice of the European Union (CJEU) in accordance with the objectives set out in the Motor Insurance Directive.
Keywords: the Court of Justice of the European Union; civil liability; vehicle; Motor Insurance Directive